Synthesis of Substituted 1,4-Benzodiazepines by Palladium-Catalyzed Cyclization of N-Tosyl-Disubstituted 2-Aminobenzylamines with Propargylic Carbonates - Masahiro Yoshida; Saya Okubo; Akira Kurosaka; Shunya Mori; Touya Kariya; Kenji Matsumoto (Molecules, 2025)
A synthesis of substituted 1,4-benzodiazepines has been developed via palladium-catalyzed cyclization of N-tosyl-disubstituted 2-aminobenzylamines with propargylic carbonates. The reaction proceeds through the formation of π-allylpalladium intermediates, which undergo intramolecular nucleophilic attack by the amide nitrogen to afford seven-membered benzodiazepine cores. In reactions involving unsymmetrical diaryl-substituted carbonates, regioselectivity was observed to favor nucleophilic attack at the alkyne terminus substituted with the more electron-rich aryl group, suggesting that electronic effects play a key role in determining product distribution. The versatility of this reaction was further demonstrated by constructing a benzodiazepine framework found in bioactive molecules, indicating its potential utility in medicinal chemistry. Mechanistic insights supported by stereochemical outcomes and X-ray crystallographic analysis of key intermediates reinforce the proposed reaction pathway. This palladium-catalyzed protocol thus offers an efficient and practical approach to access structurally diverse benzodiazepine derivatives.